Laboratory Techniques in Biochemistry and Molecular Biology:Vol. 3 - Giri, Janabai (The Indian Journal of Nutrition and Dietetics, 1979)
This volume consists of two parts. Part I written by G. G. Brownlee deals with determination of sequences in RNA. The author has given a comprehensive account of the methods available. He has taken efforts to describe the essential details such that the reader can apply the techniques without further guidance in the laboratory. The essential principles are discussed wherever necessary.